Phosphate-Solubilizing and Indole Acetic Acid-Producing Actinomycetes from the Plant Rhizosphere in the Hungayono Karst, Gorontalo - Yusriyah Yusriyah; Yuliana Retnowati; Abubakar Sidik Katili; Novri Youla Kandowangko; Wirnangsi D. Uno (Biology, Medicine, & Natural Product Chemistry, 2026)
Actinomycetes are soil microorganisms that play a crucial role in nutrient cycles and interactions, particularly in nutrient-limited environments such as karst ecosystems. This study aimed to evaluate the preliminary functional potential of actinomycetes isolated from the plant rhizosphere in the Hungayono karst ecosystem, Gorontalo, as phosphate solubilizers and producers of indole acetic acid (IAA). The study employed a quantitative descriptive approach with soil sampling at a depth of 10–15 cm using purposive sampling. Isolation was performed using the spread plate method on Starch Casein Agar medium, followed by qualitative and quantitative testing of phosphate solubilization and IAA production capabilities. Identification of selected isolates was conducted through 16S rRNA gene-based phylogenetic analysis. The results showed that 11 actinomycete isolates were obtained from 4 host plants, of which two isolates exhibited low-index qualitative phosphate solubilization activity. However, quantitative results indicated that some isolates that did not form clear zones still produced measurable amounts of soluble phosphate, suggesting differences in method sensitivity. The highest phosphate-solubilizing activity was exhibited by isolate RzPO-09. In addition, four isolates were capable of producing IAA at varying levels, with the highest production observed in isolate RzPH-07 at 0.896 ppm. Phylogenetic analysis showed that isolate RzPO-09 (PZ458677) is closely related to the genus Pseudonocardia, while RzPH-07 (PZ458434) is closely related to the genus Streptomyces. Overall, the isolates obtained show initial functional potential; however, further validation is required through optimization of culture conditions, genetic characterization, plant growth tests, and testing both in greenhouses and in the field to ensure their practical feasibility.